A Novel Technique Restores Function while Eliminating Intractable Neuropathic Pain in a 71-Year-Old Diabetic Patient under Challenging Injury Conditions - Micheo, William F.; Foy, Christian A.; Kuffler, Damien P. (Journal of Reconstructive Microsurgery Open, 2023)
Background The extent of functional recovery induced in healthy patients by sensory nerve grafts, the clinical “gold standard” technique for repairing peripheral nerves with a gap, is significantly limited by increasing gap length, time between trauma and repair, and patient age. When the values of any two, or all three, variables increase simultaneously, there is little to no recovery. For diabetic patients, even under the best of conditions and without any large variables, the extent of axon regeneration and functional recovery is significantly less, but generally none. Therefore, novel techniques are required that enhance recovery in diabetic patients.Methods A 12-cm long median nerve gap in the wrist/palm of a 71-year-old male long-term diabetic patient was bridged 1.3 years post nerve injury with a sural nerve graft within a platelet-rich plasma-filled collagen tube.Results By 2 months post-repair, the patient's level 6 chronic neuropathic pain was permanently eliminated. By 6.75 months, the palm had recovered good sensitivity to stimuli of all sensory modalities, including 4.56 g pressure and less than 15 mm two-point discrimination. Each finger had good motor function of M3–5, with partial to complete sensitivity to stimuli of all sensory modalities and an overall recovery of S3.Conclusion This technique permanently eliminates severe chronic neuropathic pain while simultaneously inducing good motor and sensory recovery in a long-term diabetic patient, under conditions where recovery is rarely, if ever, seen, even in non-diabetic patients. This technique holds great promise of restoring function to diabetic patients, for whom it is otherwise not possible.
Keywords: nerve repair; peripheral nerves; long nerve gap; neuropathic pain; platelet-rich plasma